Phase behaviour and morphology in blends of polyether and polyacrylate with the addition of lithium salt / Assoc. Prof. Dr. Sim Lai Har … [et al.] - Sim, Lai Har; Chan, Chin Han; Kammer, Hans-Werner; Hashifudin, Amirah (Research Management Institute (RMI), 2013)
Solution casting technique is employed to prepare the poly(ethylene oxide) (PEO)/ polyacrylate (PAc) blends. Thermal behaviour and ionic conductivity of the PEO/PAc and PEO/PAc blends added with LiCI04were investigated using differential scanning calorimetry (DSC) and impedance spectroscopy (IS), respectively. Observations of a single composition-dependent glass transition temperature (Tg) which agrees closely with that calculated using the Fox equation, coupled with successive suppression of the melting temperature (7m) and crystallinity of PEO with ascending PAc content, affirm the miscibility of the two constituents in the blend. The conductivity of salt-free PEO is enhanced with the addition of < 25 wt% of PAc due to the reduced crystallinity of PEO in the blend. The Tg values of the blend at all compositions under study increase with the addition of LiCI04. Ionic conductivity of the salt-added blend increases with increasing salt concentration. The amorphous phase of PEO forms the percolating pathway in the homogeneous PEO/PAc/LiCI04 blends as blends with PEO content > 25 wt% (PEO/PAc 75/25 blend) records slightly higher a values at concentration of LiCI04 (Y) > 0.02. Enhancement in ionic conductivity in the blend is probably the result of increase charge carrier density and ionic dynamic of the PEO macromolecular chain.